Discrete Element Method in the Design of Transport Systems Verification and Validation of 3D Models - Gelnar, Daniel; Zegzulka, Jiri (Springer International Publishing : Imprint: Springer, 2019)
This book deals with the design and optimization of the bucket elevator using the discrete element method (DEM). It describes the underlying scientific basis for the design of transport equipment using computer simulations and is focused on issues relevant to the industrial sector, mechanical engineering; and the transport, treatment, measurement, and storage of bulk materials. It presents solutions for mitigating bulk material supply chain interruptions due to process malfunctions and failures, utilizing research on monitoring and evaluating of the dynamic processes of particulate matter. The aim of the book is to help readers new to the field with the design of innovative devices. Imparting practical information aimed at saving time and money in project design, the book is ideal for engineers, designers, and researchers concerned with all aspects of bulk materials. Introduces and explains fully the Discrete Element Method using measured values as inputsfor the method; Shows whether calculated simulations and real measured values models can be used for design; Illustrates how to validate, calibrate, and optimize the dynamic processes of bulk elevators; Explains how to test transport and storage equipment before it is produced using dynamic simulation of material flow on transport lines, saving time and money.